Formal Security in the Works of Legal Scholars of Pre-Soviet Period - E. E. Silantyeva (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on a retrospective analysis of developments in the field of scientific and theoretical ideas about the formal security in law, suggested by legal scholars in the XIX – early XX centuries. Thus, there was already a clear understanding at that stage that legal norms were designed to accurately record the rights, obligations, certain legal consequences, and the accuracy of legal norms determined their binding nature, the specifics of sanctions, etc. The works of experts in civil studies, encyclopedia and philosophy of law have been analyzed in this way, in particular D. Grimm, N. Gredeskul, J. Pokrovsky, P. Novgorodtsev, L. Petrazhytskyi, N. Korkunov, M. Oleksiiev, Ye. Trubetskyi, G. Shershnevych and others.